Factors Affecting Customer’s Intention towards Purchasing Halal Collagen Beauty Drinks in Malaysia: a Structural Equation Modelling (Journal of Entrepreneurship and Business, 2021)
This study attempted to highlight the relationship between three factors, namely attitude, subjective norms, and knowledge of customers towards their intention to purchase Halal collagen beauty drinks. There is an increasing trend of consuming collagen beauty drink products among Malaysian women in recent years. As a Muslim nation, the sources of collagen which are mainly derived from animal parts have become a major concern for Muslim customers, especially their Halal status. In addition, the target respondents of this study were females because they are conscious of beauty and willing to buy several ranges of collagen beauty drink products in the market. The sample of the study consists of 380 Muslim female customers which were collected through self-administered questionnaires using a two-stages sampling technique. This study used a structural equation model (SEM) to develop and test the conceptual model. The results show that attitude, knowledge, and subjective norms have a significant relationship with customer purchase intention towards collagen beauty drink products.
Keywords: Array; Array; Array; Array; Array